An english-language teaching plan for children in the internet of things environment - Mohammad Moradi; Kheirollah Rahsepar Fard (Institute of Advanced Engineering and Science, 2019)
An important topic that need to investigate is teaching of English language. In most educational methods, a series of pre-defined and fixed subjects are used for all individuals. There is also less attention paid to modern methods in education of English language. In this paper we present an application as a modern method in education of English language. In the proposed algorithm that is in the internet of things environment, has paid attention to teaching of English language, includes the use of objects, images, pronunciation, the use of vocabulary in sentences and texts, the relevance of content with the age and culture of the child, and the relevance of the content of the courses and exercises with the amount of learning each child.